A morte e o morrer em contos de Perrault, irmãos Grimm e Andersen - Barbosa, Jaine De Sousa (2019)
This research of bibliographical-documentary aspect and historical-cultural matrix is arranged to understand, through a critical-interpretative reading, how was constructed the representation of death in "Blue beard" stories, collected from the book The tales of mother goose (2015), by Charles Perrault; “How children played butcher with each other I and II” published in 1812, and collected in Jacob and Wilhelm Grimm's Children's and Household Tales (1812 - 1815) (2012); and, finally, "The Child in the Grave", by Hans Christian Andersen's Tales (2011), by Andersen; the four authors are relevant names in the universe of wonderful narratives and fairy tales and have texts on the most varied themes, being quite recurrent the theme of death. In view of the fact that these narratives are inserted in different historical and temporal contexts, since the authors are from different nationalities and epochs, it has been chosen to observe the representation of death not only as an event in itself, but mainly as an event that suffers political, social, temporal and spatial influences. For this reason, it was adopted a theoretical reference that is pertinent especially to Representation and Cultural History, combined to the thought of Roger Chartier (1990) and other authors with similar epistemological orientation, in order to comprehend how is constituted the process of representation of an object, as well as of the influential ones in that process; and then it is being used studies of important names in the context of death, such as Phillipe Ariès (2012), who have shown us how man relates to the end of life. Through the elaboration of the present research, we were able to verify how different are the representations and ways of understanding death not only in the universe of literature, however in the history of humanity as a whole. Although we attach ourselves to a Eurocentric context, we realize there are many repetitions and similarities in the way of experiencing death and that in the literary universe there are many influential factors in its fictionalization, among them the historical context. In addition, we could also understand that, even though it has been a taboo for so long, death is still a controversial topic and will continue to be part of many stories, whether they are for children or not. Represented in its varied ways, it will still be a reason for fear, laughter, suffering and freedom, as it will see in the stories analyzed here.